Metabolic syndrome, small airway dysfunction and the mediating role of inflammation - Qian Xie; Shishi Xu; Qin Wan; Nanwei Tong (Scientific Reports)
Abstract Our study examined how metabolic syndrome (MetS) affects the risk of small airway dysfunction (SAD) and its progression to chronic obstructive pulmonary disease (COPD). We also investigated the role of inflammation in mediating these effects. We included 13,948 non-COPD participants, aged 40 years and with a pulmonary function test, from multiple communities (Longquan, Mianzhu, and Pidu), and subsequently followed up the Longquan community after 3 years. Logistic models estimated the association between MetS and SAD risk, adjusted for confounders. Furthermore, a mediation analysis approach was employed to estimate the proportion of effect mediated by each marker of inflammation (e.g., the low-grade inflammation index) on the observed association. In West China Natural Population Cohort Study(WCNPCS), compared to the non-MetS group, individuals with MetS showed a significantly higher prevalence of SAD (odds ratio [OR] = 1.12, 1.02–1.22); however, this was not significant in women. For MetS components, high triacylglycerols(HTG), low high-density lipoprotein cholesterol (LHDL-C) and abdominal obesity (AO) were independent risk factors for SAD, which is consistent with men (OR = 1.09–1.33). In addition, the more metabolic disorder components, the higher the prevalence of SAD (P < 0.05). Further, when MetS as well as SAD outcomes were considered together, the incidence of COPD in individuals with both these irregularities was considerably higher (9-fold). Inflammation (the proportion of effect mediated: 14.3–28.6%) played a substantial mediating role in the observed association in Chinese participants. MetS is consistently linked to SAD and may facilitate progression from SAD to COPD; its components, HTG, LHDL-C and AO, were associated with a significantly increased risk of COPD. The observed associations were partly mediated by inflammation. Treating MetS may be an effective strategy for the prevention of the development of COPD.